Nodding syndrome research, lessons learned from the NSETHIO project. (2019) - Geelhand de Merxem, D.; Siewe Fodjo, J. N.; Menon, S.; Hotterbeekx, A.; Colebunders, R.
Abstract : Background: Until recently, nodding syndrome (NS) was considered as a mysterious disease of unknown etiology. A link between onchocerciasis and epilepsy was suspected for a long time. However, onchocerciasis was not considered as the cause of NS because NS was believed to occur only in onchocerciasis-endemic regions in Uganda, South Sudan, and Tanzania. In October 2015, with funding from the European Research Council, the NSETHIO group launched a trans-disciplinary, multi-country research project to identify the cause of NS and to study the link between onchocerciasis and epilepsy. Methods: We reviewed NSETHIO activities as well as all published papers, and compared project findings with results of previous research on NS. Results: Findings from the NSETHIO project showed that NS is only one of the clinical manifestations in the wide spectrum of onchocerciasis-associated epilepsy (OAE) that could be prevented by strengthening onchocerciasis elimination programs. NSETHIO demonstrated that OAE is an important neglected public health problem in onchocerciasis-endemic areas with no or a sub-optimally functioning onchocerciasis control strategies. Conclusions: Today there is overwhelming evidence that NS together with the Nakalanga syndrome is clinical presentations of OAE, a condition that could be prevented by strengthening onchocerciasis elimination programs. While research needs to continue to elucidate the pathophysiological mechanisms causing NS, new strategies to accelerate onchocerciasis elimination coupled with community-based surveillance and treatment programs for epilepsy are urgently needed in areas of high Onchocerca volvulus transmission.